PENGARUH PEMBELAJARAN EKONOMI DENGAN METODE PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DAN THINK TALK WRITE (TTW) TERHADAP PRESTASI BELAJAR SISWA DITINJAU DARI MOTIVASI BELAJAR SISWA KELAS XI SMA N 2 SRAGEN TAHUN PELAJARAN 2012/2013 - Wihartanti, Liana Vivin; Anitah, Sri; Riani, Asri Laksmi (Jurnal Pendidikan Insan Mandiri, 2014)
Liana Vivin Wihartanti. S991108009. The Effect of Economics Learning by Cooperative Learning of Think Pair Share (TPS) and Think Talk Write (TTW) Types on The Students? Learning Performance Viewed from the Learning Motivation of the Eleventh Grade Students of Public Senior High School 2 Sragen Year 2012/ 2013. Thesis. First Consultant: Prof. Dr. Sri Anitah W., M.Pd, second Consultant: Dr. Asri Laksmi Riani, M.Si. Economics Educational Study Program, Postgraduated Program of Sebelas Maret University Surakarta. 2013.This study is aimed at finding out (1) To analyze the effect of Think Talk Write (TTW) and Think Pair Share (TPS) learning methods on the students? economic learning performance, (2) To analyze the effect of high level of learning motivation, medium level of motivation, and low level of learning motivation on the students? economics learning performance, (3) To analyze the interaction of effect between learning methods and learning motivation level on the students? economics learning performance.This study was quantitative research quasi experimental method. The population in this study included the entire eleventh grade IS students of Public Senior High School 2 Sragen of academic year 2012/ 2013, which consisted of three classes. Those three classes were XI IS 1, XI IS 2, XI IS 3, where the amount of whole population in this study was 98 students. The sampling used cluster random sampling technique. The sample in this study were XI IS 2 class, which consisted of 32 students as the experiment I class, and XI IS 3, which consisted of 33 students as the experiment II class.The data techniques of collecting data were test for economics achievement, questionnaires for students? motivation and documentation. To analyze the the hypothesis, the researcher used two-way analysis of varience with a 2x2 factorial design and the significant level was 5% . The prerequirement test in this study used normality test by Kolmogorov-Smirnov Z test and Homogeneity test with F-test.From the analysis, it can be concluded that: (1) There is effect of Think Pair Share (TPS) and Think Talk Write (TTW) toward economics learning achievement, (2) there is effect of high and low motivations toward economics learning achievement, (3) there is interaction between motivation and teaching learing types Think Pair Share (TPS) and Think Talk Write (TTW) toward economics learning achievement.Keywords: Learning motivation, learning performance, Think Pair Share, Think Talk Write.